Complement and Substitution Effects of Internal Migration on Foundational Competitiveness in Mexico - Fernández Domínguez, Amilcar Orlian; Demmler, Michael (Mercados y Negocios, 2025)
This study analyzes how internal migration among Mexican states relates to their competitiveness level. The methodology employs longitudinal panel data from 2010 to 2020 to assess how migration influences a state’s foundational competitiveness. The study’s main results are as follows: First of all, the foundational competitiveness of Mexican states, on average, increased in 2015. However, despite this increase, competitiveness in 2020 was below the 2010 level, showing a general decline experienced in the most recent years of the study sample. Secondly, the econometric results of the present study suggest that greater involvement of a highly educated migrant labor force positively affects foundational competitiveness. Furthermore, findings imply that an influx of working-age migrants may potentially contribute to the economic competitiveness of the destination state depending on differences in education levels of migrants and natives, i.e., whether immigrant human capital complements or substitutes that of the native population.